Pengaruh Inokulan Fungi Mikoriza Arbuskula dan Komposisi Media Tanam pada Pertumbuhan Tanaman Tebu (Saccharum officinarum L.) - Nia Riliana; Yonathan Parapasan; Yan Sukmawan (Fakultas Pertanian, Universitas Timor, 2020)
Sugarcane cultivation in dryland is faced with a lack of water availability and low P content in the soil. The technology that is expected to improve the productivity of dry land planted with sugar cane is the use of microbial technology, such as the arbuscular mycorrhiza fungi (AMF) which are synergized with compost planting media as a soil mixture. This study aims to obtain the optimum dose of AMF inoculants, to get the best composition of the planting media, and to get the interaction between AMF inoculant doses on the growth of sugarcane. The study was conducted at the Politeknik Negeri Lampung Teaching Farm from November 2017 to June 2018. The experiment was using a factorial randomized block design with three replications. The first factor is the AMF inoculant dose which consists of four levels (0 g/bucket, 5 g/bucket, 10 g/bucket, and 15 g/bucket); while the second factor is the composition of the compost: subsoil planting media consisting of four levels (0%: 100%, 25%: 75%, 50%: 50%, and 75%: 25%). The results showed the application of AMF inoculants up to 15 g/bucket had not been able to increase the growth of sugarcane. The composition of the planting media 25% compost: 75% subsoil has been able to increase the number of tillers, number of leaves, and stem diameter of sugarcane. There was no interaction between AMF inoculant dose and the composition of the planting media on the growth of sugarcane. Sugarcane requires fertile soil conditions, enough water, and not flooded.